KONSOLIDASI POLITIK CALON PENGHULU PEREMPUAN DALAM KONTESTASI POLITIK LOKAL DI KEPENGHULUAN SUNGAI KUBU HULU KECAMATAN KUBU KABUPATEN ROKAN HILIR TAHUN 2016 - Tri Purnawirawan; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Political consolidation is the process of combining elements of democracy to jointly facilitate political democracy. political consolidation aims to strengthen aspects of democracy in the form of political institutions or institutions, both political parties, political elites, interest groups and political communities so that the ongoing democratic arena process runs without any disabilities in its implementation. Political consolidation in the Pemulu election was seen from the local political contestation of the Kubu Hulu River Pengenguluan using the Political Consolidation Theory by Larry Diamond, namely, the elite agent / actor approach, institutional approach, political culture approach, civil society approach. Based on this theory, it can clarify the consolidation of local politics in the election contestation of the head of the 2016 Kubu Hulu River Kepenghuluan.The purpose of this study is to describe the political consolidation carried out by prospective female leaders in the simultaneous election of 2016 headners in Rokan Hilir District in Kepenghuluan Sungai KubuThe election of the headman in the Kubu Hulu River Kepenghuluan became a local political contestation in Kepenghuluan. The political consolidation of female head candidates in the election of headmen by utilizing their political power to achieve their political goals, while the political consolidation carried out by female head leaders is: a. The elite actor approach (local elite approach and non-local elite approach), b. Institutional approach (Institutional Institutional structure approach), c. Political culture approach (campaign approach, extended family approach, residence approach and religious approach) d. The approach of community organizations and the approach of political participation) in the election of the head of the 2016 Kubu Hulu River Kepenghuluan. Keywords: political consolidation, political contestation, head election